RDNA-10. TTFIELDS TREATMENT PLANNING FOR TARGETING MULTIPLE LESIONS SPREAD THROUGHOUT THE BRAIN - Naveh, Ariel (Neuro Oncol, 2019)
Tumor Treating Fields (TTFields) are approved for the treatment of Glioblastoma Multiforme (GBM) in supratentorium. When treating GBM in the suprtaentorial brain, TTFields are delivered using 2 pairs of transducer arrays positioned in close proximity to the tumor. This results in an increased TTFields dose in the affected tumor region, whilst reducing the dose in other regions, particularly the infratentorium. Brain metastases, occur in 10 to 30 percent of adults with cancer, and can occur throughout the brain, including in infratentorial regions. Therefore, when using TTFields to treat brain metastases, it is desirable to deliver TTFields at therapeutic intensities to the entire brain or to the infratentorium depending on the location of the lesions. We performed computational studies to identify array layouts for delivering TTFields at therapeutic intensities to the infratentorium and to the entire brain. The computer simulations utilized a realistic computerized head model of a 40+ years old human male prepared in-house. TTFields could be delivered effectively to the infratentorium using a layout in which a pair of arrays was placed on the lateral aspects of the neck below the ears, and the second pair on the upper head and lower neck yielded field intensities above 1 V/cm in the infratentorial brain. Other layouts in which one pair of arrays was placed on the right temple and left scapula, and the second pair placed on the left temple and right scapula yielded a uniform intensity distribution within the entire brain. This layout could be useful for treating multiple lesion spread in both the infratentorial and supratentorial regions. This study suggests that careful treatment planning could be used to optimize TTFields treatment targeting multiple lesions spread throughout the brain.